Curriculum Challenges for Universities Agenda for Change - Nyland, James; Davies, David (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book develops a progressive program of engagement with issues, problems and critical thinking which helps universities and students understand and engage with some of the key issues of our time. It focuses on curriculum concerns, and presents a sustained and critical analysis and dialogue about knowledge, culture and ways of seeing important issues. This book provides critical and analytical insights into the importance of the emergence of mass higher education into public awareness. It explores what is termed 'contested knowledge' as part of modern students' experiences and expectations. By broadcasting some of the future prospects for a democratic university, especially in relation to its communities, it highlights the need to grasp the significance of global change and instability in teaching and learning, and how an adequate curriculum in higher education can be constructed to address the issues that arise.
INTRODUCTION AND ACKNOWLEDGEMENTS -- CRITICAL THINKING AND ENGAGEMENT -- 1 Critical thinking for an engaged university -- 2 The university's social and civic role: time for an appraisal -- 3 The university as a public educator: learning and teaching for engagement -- 4 A crisis of knowledge: themes for an engaged university curriculum -- KNOWLEDGE AND CULTURE -- 5 Freedom through education: a promise postponed -- 6 Dancing in Nazareth: real knowledge beyond the boundary -- 7 A learning curriculum: exploring the professional doctorate of educational practice -- ENGAGEMENT AND DEMOCRACY -- 8 Academic and scholarly freedom: towards a 'disputing' university with critically engaged students -- 9 Ways of knowing: towards an ecology of learning and community -- 10 Towards a 21st century approach to civic engagement locally and globally: a conversation between Professor James Nyland and Professor Richard Teare -- THE FUTURE: SLOW BURN OR FAST FORWARD -- 11 The burning world: transformation and sustainability or apocalypse? -- 12 Indigenous knowledge in Australia: imagining a different society -- 13 The new normal after coronavirus: is there anyone here from education? -- CONCLUSION -- 14 Learning that matters.
Keywords: Education, Higher; Education and state; Educational sociology; Education-Curricula.; Higher Education; Educational Policy and Politics; Sociology of Education; Curriculum Studies